2005
DOI: 10.1596/1813-9450-3776
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects And Pesticide Perception As Determinants Of Pesticide Use : Evidence From Bangladesh

Abstract: In a recent survey of 820 Boro (winter rice), potato, bean, eggplant, cabbage, sugarcane and mango farmers in Bangladesh, over 47% of farmers were found to be overusing pesticides. With only 4% of farmers formally trained in pesticide use or handling, and over 87% openly admitting to using little or no protective measures while applying pesticides, overuse is potentially a very threatening problem to farmer health as well as the environment.To model pesticide overuse, we used a 3-equation, trivariate probit fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 8 publications
3
75
0
2
Order By: Relevance
“…In contrast, Rahman [25,26] noted significantly positive influence of education on pesticide use in Bangladesh. However, Idris et al [24], Rahman [4], and Dasgupta et al [33] did not find any significant influence of education on pesticide use in Bangladesh. The implication is that the influence of education on pesticide use is somewhat mixed in the literature.…”
Section: Determinants Of Pesticide Use In Food Cropsmentioning
confidence: 98%
“…In contrast, Rahman [25,26] noted significantly positive influence of education on pesticide use in Bangladesh. However, Idris et al [24], Rahman [4], and Dasgupta et al [33] did not find any significant influence of education on pesticide use in Bangladesh. The implication is that the influence of education on pesticide use is somewhat mixed in the literature.…”
Section: Determinants Of Pesticide Use In Food Cropsmentioning
confidence: 98%
“…Information about the quantity and the identity of all types of pesticides those have been using in this country is virtually unavailable [8][9][10][11]. One important issue can be noticed that many pesticides are being used or still being produced in this country are already banned and/or restricted under international agreements [12,13] e.g., DDT for instance [14][15][16]. On the other hand, statistical database called 'FAOSTAT' of Food and Agriculture organization (FAO) of United Nations (UN) can provide some reasonable data for the country [17] but conflicting information can be noticed from the above cited sources [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…They also reported some short-term diseases such as skin diseases, eye diseases, gastro-intestinal diseases, and urinary and reproduction impairment, probably related to pesticide use. Another study including 821 farmers among 11 districts in Bangladesh showed some negative symptoms after pesticide application such as headache (27%), dizziness (8%), eye irritation (26%), skin disease (13%), vomiting (9%) and other multiple diseases (Dasgupta et al, 2005 For instance, the government should launch education programs for farmers. The Department of Agricultural Extension (DAE), the largest agro-based public organization, is mainly responsible for providing extension services through Sub-Assistant Agricultural Officer (SAAO), a person who live in the farming village and visits local farms individually and in group meetings.…”
Section: Farmers' Perceptions On Pesticide Risks and Occupational Heamentioning
confidence: 99%
“…As a consequence, pesticides are being used to protect rice crops from pests, herewith improving rice crop yields and the quality of the product (Ansara-Ross et al, 2012;Rahman, 2013). As in many developing countries, the government has promoted the use of pesticides to increase agricultural yields in Bangladesh (Dasgupta et al, 2005). Pesticide consumption in Bangladesh has dramatically increased from 7,350 metric tons in 1992 to 45,172 metric tons in 2010 (Hasan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation